2022
DOI: 10.3390/jcm11030537
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid/Collagenase Ointment in the Treatment of Chronic Hard-to-Heal Wounds: An Observational and Retrospective Study

Abstract: Background: Wound bed preparation is an important concept in clinical practice and is related to adequate debridement. The use of proteolytic enzymes is an established method of enzymatic wound debridement, especially in hard-to-heal ulcers that are unresponsive to normal healing procedures and progress. The TIME framework (tissue, inflammation/infection, moisture balance, and edge of wound) offers an appropriate strategy to eliminate resistance to healing, as well as maximizing the healing process. Maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Furthermore, a clinical evaluation of the skin trophism was conducted during the follow-up sessions, with significant improvements observed compared to the baseline properties. The results are in line with previous studies, revealing the structural remodeling potential of PRP [46], leading to the disposal of hyaluronic acid and glycosaminoglycan expression as well as modulate matrix metalloproteinase and tissue inhibitor metalloproteinase equilibrium [47,48].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a clinical evaluation of the skin trophism was conducted during the follow-up sessions, with significant improvements observed compared to the baseline properties. The results are in line with previous studies, revealing the structural remodeling potential of PRP [46], leading to the disposal of hyaluronic acid and glycosaminoglycan expression as well as modulate matrix metalloproteinase and tissue inhibitor metalloproteinase equilibrium [47,48].…”
Section: Discussionsupporting
confidence: 92%
“…The study observed a minimal to 100% reduction in wound size, notably diminished exudate excretion, healthy wound edge, and lower pain score. 9 Nosseir et al, (2018) compared between the effectiveness of estrogen iontophoresis as physical therapy modality and stem cell therapy in the treatment of diabetic foot ulcers. Results showed that estrogen iontophoresis for 4 weeks in combination with stem cell is an effective adjuvant therapy, better that each method alone, in treatment of diabetic foot ulcers through accelerating wound healing and reducing WSA, wound volume.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Enzymatic debridement dressing: Enzymatic debridement is a method that uses chemical reagents to identify and break down inactivated tissue, usually in smaller wounds and wounds with selective microenvironments that do not require intervention. Enzymatic debridement dressing has the advantages of being cost-effective and efficient [ 49 , 50 ]. (3) Antiseptic dressings: Some research suggests that debridement alone is not sufficient to accelerate chronic wound healing and recommends the use of antiseptics to complement the debridement process and control infection.…”
Section: Diabetic Wounds and Diabetic Dressingsmentioning
confidence: 99%